Study of disease pattern of patients admitted in Gynae & Obst. Department in a rural tertiary medical institute - Sultana, Mst Atia; Akter, Monira; Noor, Tahmina; Hossain, Mahbub (KYAMC Journal, 2013)
The aim of this study was to find out the Gynaecological disease pattern, common diseases, age distribution , organs involvement of female reproductive system, types of diseases etc. in admitted patient of Khwaja Yunus Ali Medical College & Hospital (KYAMCH) a rural tertiary hospital in Bangladesh. In this retrospective & descriptive study total 853 Gynaecological patients were evaluated in 4 years period, who were admitted either from OPD or through emergency. Most of the diagnosis were made after evaluation of organ involvement, 53% uterine origin, most are benign 29%; 40% patient having normal menstrual cycle but suffering from Gynaecological diseases like chronic cervicitis, lower abdominal pain(PID). Vaginal discharge, urinary tract infection, ectopic pregnancy, different types of abortion. This study showed that the Gynaecological disease pattern of Patients admitted in Obs& Gynae department of KYAMCH- a rural tertiary medical institute. DOI: http://dx.doi.org/10.3329/kyamcj.v3i1.13656 KYAMC Journal Vol. 3, No.-1, June 2012 pp.220-222